Cumulative lifetime stressor exposure and health in elite athletes: the moderating role of perfectionism - McLoughlin, E.; Fletcher, D.; Graham, H. L.; Arnold, R.; Madigan, D. J.; Slavich, G. M.; Moore, L. J. (International Journal of Sport and Exercise Psychology, 2024)
Although greater lifetime stressor exposure has been associated with physical and mental health issues in the general population, relatively little is known about how lifetime stressors impact the physical and mental health of elite athletes or the factors moderating this association. Given that many elite athletes show signs of perfectionism, and that this trait has been linked with ill-health, it is possible that perfectionism may moderate the lifetime stressor-health relationship. To test this possibility, we examined how cumulative lifetime stressor exposure was associated with general mental and physical health complaints in elite athletes, and the extent to which these associations were moderated by perfectionism. Participants were 110 elite athletes (64 female; Mage = 29.98 years, SD = 10.54) who completed assessments of lifetime stressor exposure, physical health, psychological distress, and perfectionism. As hypothesised, hierarchical regression analyses revealed that experiencing more severe lifetime stressors was related to poorer physical and mental health. Furthermore, self-oriented perfectionism moderated the association between lifetime stressor count and severity and physical health, but not mental health. Overall, these data demonstrate stressor-specific effects among elite athletes and highlight the potential importance of assessing lifetime stressor exposure and perfectionistic tendencies in order to improve athlete health and well-being.